2013
DOI: 10.1111/apha.12071
|View full text |Cite
|
Sign up to set email alerts
|

Temporal alterations and cellular mechanisms of transmural repolarization during progression of mouse cardiac hypertrophy and failure

Abstract: The two distinct TDR modes were revealed during the progression of mouse cardiac hypertrophy and failure, indicating that the remodelling of TDR depends on the stage of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 43 publications
5
15
0
Order By: Relevance
“…The failing heart phenotype is characterized by distinct alterations in selected ion channels, changes in intracellular calcium cycling, alterations in cell-cell coupling proteins, enhanced interstitial fibrosis, and cellular hypertrophy [5][7]. Experimental studies in animal models provide evidence for enhanced repolarization gradients in the setting of the failing heart [8], [9] and these can promote reentrant arrhythmias. However, recent studies performed using explanted failing human hearts [6], [10], [11] provide little evidence for these enhanced repolarization gradients.…”
Section: Introductionmentioning
confidence: 99%
“…The failing heart phenotype is characterized by distinct alterations in selected ion channels, changes in intracellular calcium cycling, alterations in cell-cell coupling proteins, enhanced interstitial fibrosis, and cellular hypertrophy [5][7]. Experimental studies in animal models provide evidence for enhanced repolarization gradients in the setting of the failing heart [8], [9] and these can promote reentrant arrhythmias. However, recent studies performed using explanted failing human hearts [6], [10], [11] provide little evidence for these enhanced repolarization gradients.…”
Section: Introductionmentioning
confidence: 99%
“…23 From a histopathological point of view, it has been shown that fiber disarray and/or fibrosis are correlated with the occurrence of TWA and VT in HCM. Kon-no et al 9 investigated TWA in 12 patients with HCM and LV hypertrophy and found that TWA may be related to an abnormal myocardial disarray and/or fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The abnormality that is most consistently found in animal models of cardiac hypertrophy is the prolongation of the APD [2325]. Ca 2+ plays a key role in the excitation-contraction coupling and the activation of Ca 2+ -dependent signalling pathways.…”
Section: Discussionmentioning
confidence: 99%